2017
DOI: 10.1073/pnas.1701824114
|View full text |Cite
|
Sign up to set email alerts
|

Redox-dependent interaction between thaumatin-like protein and β-glucan influences malting quality of barley

Abstract: Barley is the cornerstone of the malting and brewing industry. It is known that 250 quantitative trait loci (QTLs) of the grain are associated with 19 malting-quality phenotypes. However, only a few of the contributing genetic components have been identified. One of these, on chromosome 4H, contains a major malting QTL, QTL2, located near the telomeric region that accounts, respectively, for 28.9% and 37.6% of the variation in the β-glucan and extract fractions of malt. In the current study, we dissected the Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 37 publications
3
58
2
Order By: Relevance
“…The interaction has been found to be redox-dependent. [44] Since barley is mostly used in the brewing industry, during the breeding and genetic improvement process, the effect of genes which are coding for β-glucan synthesis could be automatically depleted. Due to low genetic influence for β-glucan synthesis, cultivated varieties may record a lower amount of β-glucan than wild barley accessions.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction has been found to be redox-dependent. [44] Since barley is mostly used in the brewing industry, during the breeding and genetic improvement process, the effect of genes which are coding for β-glucan synthesis could be automatically depleted. Due to low genetic influence for β-glucan synthesis, cultivated varieties may record a lower amount of β-glucan than wild barley accessions.…”
Section: Discussionmentioning
confidence: 99%
“…The lowering of beta‐glucan levels in response to single and combined stress in variety Garnet is particularly interesting. It has been reported that stress‐induced thaumatin‐like proteins bind to beta‐glucans and facilitate their removal during malting (Singh et al ). It is tempting to speculate that an increase in protein levels in Garnet may be contributing to the lowering of the beta‐glucan levels in this variety.…”
Section: Discussionmentioning
confidence: 99%
“…In Plants, TLPs are members of the PR-5 gene family that includes permatin, osmotin, osmotin-like proteins (OLPs), synthesis of which is mainly triggered in response to biotic and abiotic stress. However, it is also developmentally regulated during seed germination [1] and fruit ripening [2], which perform defense and development related functions 93 [3].…”
Section: Introductionmentioning
confidence: 99%
“…TLPs have roles in plant development and physiology, including tolerance to freezing stress [12] , antifungal activity [11], fruit ripening [13] and seed germination [14]. TLPs have been identified in various plants including Moss (Physcomitrella), Arabidopsis, Rice, Maize, Poplar and Barley [1,5,15].…”
mentioning
confidence: 99%
See 1 more Smart Citation